ANALISIS PENGARUH RETURN ON ASSETS (ROA), DEBT TO EQUITY RATIO (DER), DAN CURRENT RATIO (CR) TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Widyantini, Dian; Affar, Muhammad; Suherman, Ujang; Lismaryanti, Lismaryanti; Irawaty, Rosalia (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on stock prices on the Indonesia Stock Exchange. This study uses an associative research method with a quantitative approach. The sampling technique used in this study is purposive sampling, so that a sample of 32 companies can be obtained that meet the criteria. The analytical method used in this study is multiple linear regression analysis using the SPSS program. The results of this study indicate that partially, Return on Assets (ROA) has a significant effect on stock prices. Debt to Equity Ratio (DER) does not have a significant effect on stock prices. Current Ratio (CR) does not have a significant effect on stock prices. Simultaneously, Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) affect stock prices.